Laparoscopic management of large benign ovarian cysts - G., Ashwini Sidhmalswamy; Ghongdemath, Jyoti S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Laparoscopy has become an accepted method of management of ovarian cysts. Objective of present study was to assess the feasibility and outcome of laparoscopic surgery for the management of large ovarian cysts. Methods: Ten patients from May 2014 to April 2015, with large ovarian cysts, with diameter >10 cm, were managed laparoscopically. All the masses were cystic and were not associated with ascites or enlarged lymph nodes on ultrasound. Serum CA 125 levels were within the normal range (0-35 U/mL). Preoperative evaluation included history, clinical examination, sonographic images and serum markers. The management of these ovarian cysts included aspiration, cystectomy or salphingo-oophorectomy, depending on the patient’s age, obstetric history and desire of future fertility. Results: Seven patients presented with pain abdomen, 3 patients with abdominal distension and discomfort. The average maximum diameter of the ovarian cysts was 14.75 cm (range, 10-22 cm). The mean duration of the operation was 80 minutes (60 -120 min). The postoperative hospital stay was 2 days. No intraoperative complications occurred, and the hospital course of all patients was uncomplicated. The patients did not report any complaints during follow-up and the clinical examination findings were normal in all, up to 9 months after discharge. Conclusions: With proper patient selection, the size of an ovarian cyst is not necessarily a contraindication for laparoscopic surgery.